2020
DOI: 10.3390/cancers12071964
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Extracellular Vesicles in the Glioma Microenvironment: Biogenesis and Clinical Relevance

Abstract: Gliomas are a diverse group of brain tumors comprised of malignant cells (‘tumor’ cells) and non-malignant ‘normal’ cells, including neural (neurons, glia), inflammatory (microglia, macrophage) and vascular cells. Tumor heterogeneity arises in part because, within the glioma mass, both ‘tumor’ and ‘normal’ cells secrete factors that form a unique microenvironment to influence tumor progression. Extracellular vesicles (EVs) are critical mediators of intercellular communication between immediate cellular neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 209 publications
(310 reference statements)
0
17
0
Order By: Relevance
“…The release of EVs from tumor cells supports the ability of GBs to communicate with distant cells. Interestingly, the content of EVs reflects the activation state of the mother cell; hence, tumor cells can proliferate and modulate acceptor cells (Matarredona and Pastor, 2019;Zhang et al, 2019;Schuurmans et al, 2020). Studies of EVs are emerging and have shown promising results regarding their ability to maintain a propitious niche for tumor development, as they can modulate immune, epithelial, and glial cell signaling (Benito-Martin et al, 2015;Whiteside, 2017;Almeida et al, 2019;Boomgarden et al, 2020).…”
Section: Adenosinergic Signaling In Glioblastoma Microenvironmentmentioning
confidence: 99%
“…The release of EVs from tumor cells supports the ability of GBs to communicate with distant cells. Interestingly, the content of EVs reflects the activation state of the mother cell; hence, tumor cells can proliferate and modulate acceptor cells (Matarredona and Pastor, 2019;Zhang et al, 2019;Schuurmans et al, 2020). Studies of EVs are emerging and have shown promising results regarding their ability to maintain a propitious niche for tumor development, as they can modulate immune, epithelial, and glial cell signaling (Benito-Martin et al, 2015;Whiteside, 2017;Almeida et al, 2019;Boomgarden et al, 2020).…”
Section: Adenosinergic Signaling In Glioblastoma Microenvironmentmentioning
confidence: 99%
“… 49 , 52 , 53 Conversely, CSF is a confined compartment that is shielded from the blood by the BBB. It is less in volume and contains fewer EVs from other sources compared to blood 54 ; however, CSF sampling is achievable only through lumbar puncture, which is invasive, painful, distressing, and carries the risk of infection and cerebral herniation, among others. These aspects make it inadvisable to repeat CSF sampling in a close timeframe, while supporting blood as the preferred liquid biopsy sample medium.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Analyzing the spatial distribution of a target molecule within or around an EV of interest is also currently limited as there are no well-established counterstain equivalents used in the immunofluorescence imaging of adherent cells as EVs generally lack a nucleus or nuclear content and even an actin cytoskeleton. The use of orthogonal techniques such as transmission electron microscopy or mass cytometry may help address or mitigate these limitations [ 146 ].…”
Section: Extracellular Vesiclementioning
confidence: 99%